Impact of Heating Temperature and Fatty Acid Type on the Formation of Lipid Oxidation Products During Thermal Processing - Zhuang, Yuan; Dong, Jun; He, Xiaomei; Wang, Junping; Li, Changmo; Dong, Lu; Zhang, Yan; Zhou, Xiaofei; Wang, Hongxun; Yi, Yang; Wang, Shuo (Frontiers in Nutrition, 2022)
Thermal treatment of lipids rich in fatty acids contribute to the formation of lipid oxidation products (LOPs), which have potentially harmful effects on human health. This study taken soybean oil (SO), palm oil (PO), olive oil (OO), and lard oil (LO) as the research object, aimed to investigate the impact of heating temperature and fatty acid type on the generation of LOPs (α-dicarbonyl compounds, malondialdehyde (MDA), α,β-unsaturated aldehydes, and 16 volatile aldehydes). Results showed that LOPs increased significantly (P < 0.05) with the increase of temperature (100 ~ 200℃). Furthermore, the amount of 2,3-butanedione (159.53 μg/g), MDA (3.15 μg/g), 4-hydroxy-hexenal (3.03 μg/g), 2-butenal (292.18%), 2-pentenal (102.26%), hexanal (898.72%), and 2,4-heptadienal (E, E) (2182.05%) were more at 200oC in SO rich in polyunsaturated fatty acids (PUFAs) than other oils. Results from heat map analysis indicated that the 2, 4-heptadienal and glyoxal related to the myristic acid of oil. Moreover, the MDA was in close association with PUFAs. Based on the effect of temperature and fatty acid type on the generation of LOPs, this study could serve as a control method to reduce harmful LOPs.